The cultural aspects of MINT recruitment. - Günther, Benjamin (Diplomica Verlag, 2014)
This study is based upon the assumption that in case of a shrinking workforce supply in the scope of a possible skills shortage, employers would have to adjust their offers in order to attract job candidates. Although, this topic already is being paid widespread public and scholar attention, this book is the first to include cultural aspects into the discussion. The book's focus is on the German labor market. However, it contains findings which are generally applicable. As in Germany the public debate is focused on the MINT sector, the scope of the examination is limited to exactly this part o.